Purification of interferon alfa-2b using ionic liquid-based technologies - Castro, Leonor S. (2022)
The development of protein-based biopharmaceuticals and their introduction on modern medicine brought enormous benefits to the treatment of life-threatening diseases such as cancer, diabetes and neurodegenerative disorders. However, their current high-cost still limits their widespread use. While significant advances at the upstream level have occurred, current purification strategies are unable to cope with high product concentrations resorting to cost-effective approaches. This work entails the development of sustainable downstream processing methodologies for recombinant interferon (IFN) α-2b derived from Escherichia coli using ionic liquids, either by exploring their application as adjuvants in polymer-polymer aqueous two-phase systems (ATPS) or as chromatographic ligands covalently attached in silica (supported ionic liquids - SILs). Overall, our results demonstrate the high potential exhibited by ionic liquids toward the preparative purification of the recombinant IFN α-2b biopharmaceutical.